2020
DOI: 10.1017/hpl.2020.26
|View full text |Cite
|
Sign up to set email alerts
|

A Yb:KGW dual-crystal regenerative amplifier

Abstract: This study develops a Yb:KGW dual-crystal based regenerative amplifier. The thermal lensing and gain-narrowing effects are compensated by the dual-crystal configuration. Sub-nanojoule pulses are amplified to 1.5 mJ with 9 nm spectral bandwidth and 1 kHz repetition rate using chirped pulse amplification technology. Consequently, 1.2 mJ pulses with a pulse duration of 227 fs are obtained after compression. Thanks to the cavity design, the output laser was a near diffraction limited beam with M2 around 1.1. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Pouysegur et al reported on a Yb:KYW regenerative amplifier which generated 0.01 mJ pulses with a duration of 145 fs [3]. Average output energy of 1.2 mJ based on Yb:KGW dual-crystal regenerative amplifier at a repetition rate of 1 kHz with a pulse width of 227 fs has been reported by He et al [4]. P. Sevillano et al presented a diode pumped ultrafast amplifier based on Yb:CaF2 which delivered 32 mJ energy at a repetition rate of 200 Hz with a pulse width of 300 fs [5].…”
Section: Introductionmentioning
confidence: 84%
“…Pouysegur et al reported on a Yb:KYW regenerative amplifier which generated 0.01 mJ pulses with a duration of 145 fs [3]. Average output energy of 1.2 mJ based on Yb:KGW dual-crystal regenerative amplifier at a repetition rate of 1 kHz with a pulse width of 227 fs has been reported by He et al [4]. P. Sevillano et al presented a diode pumped ultrafast amplifier based on Yb:CaF2 which delivered 32 mJ energy at a repetition rate of 200 Hz with a pulse width of 300 fs [5].…”
Section: Introductionmentioning
confidence: 84%
“…Architectures based on Ytterbium (Yb 3+ ) doped gain medium with high quantum efficiency have achieved impressive results with high-power ultra-short pulse lasers pumped by highpower semiconductor laser diodes(LD) [7][8][9][10], among which bulk Yb 3+ doped crystal lasers have attracted much attention due to low cost, compactness and high efficiency [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, we demonstrated a diode-pumped SESAM mode-locked Yb:KGW oscillator, which delivered 160 fs pulse with 7.6 W of average output power [21] . The Yb:KGW crystal can be used not only to generate highpower laser but also to obtain large energy laser [27,28] . In 2020, the Yb:KGW regenerative amplifier delivering 227 fs pulses with single pulse energy of 1.2 mJ at the repetition frequency of 1 kHz after compression was reported [28] .…”
Section: Introductionmentioning
confidence: 99%
“…The Yb:KGW crystal can be used not only to generate highpower laser but also to obtain large energy laser [27,28] . In 2020, the Yb:KGW regenerative amplifier delivering 227 fs pulses with single pulse energy of 1.2 mJ at the repetition frequency of 1 kHz after compression was reported [28] . Thus, it can be seen that the higher average power is usually achieved at the cost of a longer pulse.…”
Section: Introductionmentioning
confidence: 99%